Surface Diatoms and Water Quality of Balekambang Lake Dieng, Java Indonesia - Widyanta, Christopher Hardian; Soeprobowati, Tri Retnaningsih; Jumari, Jumari; Hariyati, Riche; Falah, Mirza Hanif Al; Heijnis, Hendrik (Iraqi Journal of Science, 2025)
Bacillariophytes or well known as Diatoms, are single-celled microalgae, identified by their unique characteristic siliceous cell walls, which are well preserved in sediment as a microfossil. Diatom abundance represented the environmental condition when they lived. Balekambang Lake is one of many small lakes in Dieng; it has a unique characteristic: floating soil. The problem in Baekambang Lake is the shrinkage part of the lake area due to the sedimentation rate form the hill around with potato farming. This study aims to analyse the community of surface diatoms and water quality of Balekambang Lake, Dieng. The surface sediment samples were collected from five different sites; then, the digestion, preparation, and identification of diatoms were performed. The results obtained 103 species of diatoms dominated by the genus Pinnularia and Nitzschia. The results of the diversity index (H'), dominance index (D), and evenness index (e) show that the condition of the ecosystem in Balekambang Lake is still relatively stable. The abundance of Pseudostaurosiropsis connecticutensis and Nitzschia palea indicates that the lake is undergoing a process of eutrophication.